Neonatal Kasabach-Merritt Syndrome (KMS): case report - Kumar Rathia, Santosh; Phuljhele, Sharja; Gandhi, Animesh (International Journal of Medical Research and Review, 2016)
A 2days baby girl presented with congenital reddish-blue swelling over chest and abdomen with thrombocytopenia. The clinical, imagining and laboratory findings suggested the diagnosis of KMS. Oral steroid was started with initially needed platelet and FFP transfusions. Large thoracic hemangioma was non-amenable to surgical and radiological interventions. Vincristine was initiated after 2week trial of Prednisolone for persistent thrombocytopenia and non-regressing haemangioma. Over a week the lesion shrunk with improving platelet count. Vincristine was stopped after 4weeks in view of no further tumour shrinkage. The patient was discharged on steroid advised for 6-12 months and showed significant tumour regression at 3month.